PENERAPAN PRINSIP SYARIAH DALAM PEYELENGGARAAN LAYANAN PINJAM-MEMINJAM BERBASIS FINTECH - Basrowi Basrowi; Julianas Julianas (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This study aims to describe the application of sharia principles in the implementation of fintech-based lending services. The method used in this study is descriptive qualitative research and literature. The data used is secondary data from various relevant and up to date literature. Based on the results of the analysis it can be concluded that accounts payable is an agreement between two parties giving money or goods to a second party to be utilized. In terms of engagement in accordance with Islamic law or according to sharia, contracts through information technology media still have to fulfill harmony and terms of contract. The contract scheme implemented by service providers includes the Wakalah bil Ujrah contract and the Musyarakah contract. In the field of muamalah known as the principle of Islamic law, namely the principle of skill or change. The terms of Ijab Qobul must describe the agreement of the parties to enter into the online debt agreement. To achieve this, it is necessary to apply the principles of Islamic engagement, sharia, into financial transactions and other businesses that are consistently related.Keywords: financial technology, sharia, principleREFFERENCESAdrian Sutedi. (2009). Perbankan Syariah: Tinjauan dan Beberapa Segi Hukum. Jakarta: Ghalia.Alwi, A. B. (2018). Pembiayaan Berbasis Teknologi Informasi (Fintech) yang Berdasarkan Syariah. Al-Qanun: Jurnal Pemikiran Dan Pembaharuan Hukum Islam, 21(2), 255–271. Retrieved from http://jurnalfsh.uinsby.ac.id/index.php/qanun/article/view/684Andreas, D. (2018). OJK Bakal Segera Buat Aturan untuk Mengawasi Fintech Syariah. Retrieved from https://ummatpos.com/19750/fintech-syariah-butuh-landasan-fatwa-dan-panduan-ulamaArno Maierbrugger. (2018). A new term is born : Shariah fintech , and it has quite some potential. Retrieved from https://www.gulf-times.com/story/599050/A-new-term-is-born-Shariah-fintech-and-it-has-quit%0AABusro, Muhammad. 2018. Metode Penelitian Sosial. Surabaya: Jenggala Pustaka UtamaDewan Syariah Nasional (DSN) No 117/DSN-MUI/II/2018 Tentang Layanan Pembiayaan Berbasis Teknologi Informasi Berdasarkan Prinsip SyariahM. Ali Hasan. (2018). Pengantar Lembaga Keuangan Syariah. Surabaya: FH UNAIR SURABAYA. Retrieved from https://genap2019.aula.unair.ac.id/login/index.php Usanti,Micu, A. (2016). Fintech And Its Implementation On The Romanian Non-Banking, IV(2), 379–384. Retrieved from seaopenresearch.eu/Journals/articles/SPAS_11_30.pdfMuchlis, R. (2018). Analisis SWOT Financial Technology (Fintech) Pembiayaan Perbankan Syariah Di Indonesia (Studi Kasus 4 Bank Syariah Di Kota Medan). AT-TAWASSUTH: Jurnal Ekonomi Syariah, 1(1), 335–357.Mukhlisin, M. (2016). Dibalik FinTech Syariah. Retrieved from https://www.islampos.com/55845-55845/%0ADibalikMurniati. (2017). Fintech Syariah Butuh Landasan Fatwa Dan Panduan Ulama. Retrieved from https://ummatpos.com/19750/fintech-syariah-butuh-landasan-fatwa-dan-panduan-ulama/%0AFintechPashafollow, M. R. (2017). Potensi Besar Perkembangan Fintech Berbasis Syariah di Masa Depan.Samir, S., & Rahmizal, M. (2017). Developing Islamic Financial Technology In Indonesia, 1(2), 130–140. https://doi.org/10.26487/hebr.vSari, A. R. (2018). Perlindungan Hukum Bagi Pemberi Pinjaman Dalam Penyelenggaraan Financial Technology Berbasis Peer To Peer Lending Di Indonesia. Yogyakarta. Retrieved from http://e-journal.uajy.ac.id/14649/1/Jurnal.pdfTrisadini P. Usanti. (2004). Penanganan Pembiayaan Bermasalah Di Bank Syariah. Yuridika, 19(1).Trisadini UP dan Abdul Shomad. (2015). Hukum Perbankan. Surabaya: FH- Universita Airlangga dan Lutfansah Media.Umi Kulsum. (2018). Dewan Syariah dan OJK segera rilis fatwa fintech syariah, (November 2017), 2018.